SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PELATIH KEGIATAN EKSTRAKURIKULER MENGGUNAKAN METODE MOOSRA - Arya Widana; Volvo Sihombing; Ibnu Rasyid Munthe (Politeknik Bisnis Indonesia, 2023)
This research aims to solve the problem of selecting extracurricular coaches. To assist the Faculty of Science and Technology at Labuhanbatu University in selecting trainers for extracurricular activities, a Decision Support System was designed using the MOOSRA (Multi-Objective Optimization based on Ratio Analysis) method. The Decision Support System (DSS) using the MOOSRA method was implemented to increase objectivity and efficiency in selecting trainers. Research methods include preliminary studies, determining criteria (experience, achievement, academics, skills, leadership), and data collection. MOOSRA is used to optimize decisions based on criteria. The ranking results show the three best coaches: Coach02, Coach08, and Coach07. The existence of this decision support system can help make it easier for the Faculty of Science and Technology, Labuhanbatu University, to select extracurricular trainers more quickly and efficiently so that they can support and increase effectiveness in supervising student extracurricular activities.